Customer perception about quality of service : the case of Vietnamese and Australian managers / George O. Tasie - O. Tasie, George (Faculty of Business and Management ; UiTM Press, 2002)
Satisfied customers are of paramount importance to creating and maintaining a sustainable advantage in the highly contemporary competitive business environment. Other forms of competitive advantage are easily lost, or copied by competitors. Consequently, customer satisfaction and service quality have been of considerable interest to both researchers and practitioners over the last two decades, and a substantial body of formal academic work has emerged to address these issues. However, comparatively little work has been carried out to date in studying what managers of business actually do in practice to measure, and consequently, manage their customer satisfaction and service quality, and less work has also been done internationally to ascertain differences in perception. This research paper reports the results of a comparative study of manager's perceptions of their customers' opinions of service quality in Australia (as an example of a eveloped country) and Vietnam (as an example of a developing country in transition to a free market economy).